Individual and social determinants of shiftwork tolerance - Nachreiner, F. (Scandinavian Journal of Work, Environment & Health, 1998)
This paper reviews evidence published on individual and social determinants of shiftwork tolerance since 1993. In agreement with earlier reviews, individual differences show only some low and inconsistent concurrent covariation with shiftwork tolerance, and no predictive power for these measures has been found. It is thus not possible to predict future shiftwork tolerance from individual differences. Social conditions are also related to shiftwork tolerance, although again predictive power has not been demonstrated. An examination of the reasons for this state of the art suggested means of improving the relevance and usability of future research in this area.
Keywords: individual differences; research strategy; selection; shift work; social condition